Indirect rapid prototyping of sol-gel hybrid glass scaffolds for bone regeneration – Effects of organic crosslinker valence, content and molecular weight on mechanical properties. (15th April 2016) - Hendrikx, Stephan; Kascholke, Christian; Flath, Tobias; Schumann, Dirk; Gressenbuch, Mathias; Schulze, F. Peter; Hacker, Michael C.; Schulz-Siegmund, Michaela
Graphical abstract: Abstract: We present a series of organic/inorganic hybrid sol-gel derived glasses, made from a tetraethoxysilane-derived silica sol (100% SiO2 ) and oligovalent organic crosslinkers functionalized with 3-isocyanatopropyltriethoxysilane. The material was susceptible to heat sterilization. The hybrids were processed into pore-interconnected scaffolds by an indirect rapid prototyping method, described here for the first time for sol-gel glass materials. A large panel of polyethylene oxide-derived 2- to 4-armed crosslinkers of molecular weights ranging between 170 and 8000 Da were incorporated and their effect on scaffold mechanical properties was investigated. By multiple linear regression, 'organic content' and the 'content of ethylene oxide units in the hybrid' were identified as the main factors that determined compressive strength and modulus, respectively. In general, 3- and 4-armed crosslinkers performed better than linear molecules. Compression tests and cell culture experiments with osteoblast-like SaOS-2 cells showed that macroporous scaffolds can be produced with compressive strengths of up to 33 ± 2 MPa and with a pore structure that allows cells to grow deep into the scaffolds and form mineral deposits. Compressive moduli between 27 ± 7 MPa and 568 ± 98 MPa were obtained depending on the hybrid composition and problems associated with the inherent brittleness of sol-gel glass materials could be overcome. SaOS-2 cells showed cytocompatibility on hybrid glass scaffolds and mineral accumulation started as early as day 7. On day 14, we also found mineral accumulation on control hybrid glass scaffolds without cells, indicating a positive effect of the hybrid glass on mineral accumulation. Statement of Significance: We produced a hybrid sol-gel glass material with significantly improved mechanical properties towards an application in bone regeneration and processed the material into macroporous scaffolds of controlled architecture by indirect rapid prototyping. We were able to produce macroporous materials of relevant porosity and pore size with compressive moduli, covering the range reported for cancellous bone while an even higher compressive strength was maintained. By multiple linear regression, we identified crosslinker parameters, namely organic content and the content of ethylene oxide units in the hybrids that predominantly determined the mechanics of the hybrid materials. The scaffolds proved to be cytocompatible and induced mineralization in SaOS-2 cells. This provides new insight on the critical parameters for the design of the organic components of covalent hybrid sol-gel glasses.